Qualitative analysis of factors associated with the experience of contraception in rural setting - Črnigoj, Špela (Obzornik zdravstvene nege, 2016)
Introduction: The phenomenon of contraception, its prevalence and its implication for women's emancipation is influenced by a number of social factors, including the environment. The purpose of this study was to examine the phenomenon of contraception through the eyes, knowledge, experience and perception of women living in rural areas. Methods: The phenomenological approach was used within the framework of qualitative methodology. The purposive sample included eight women aged 20 to 50 years, living in the rural areas of western Slovenia. The research was conducted in April and May 2015. The data obtained through semi-structured interviews were analysed using the method of phenomenological text analysis. Results: The analysis yielded four thematic groups which conceptualize the studied phenomenon: (1) the factors affecting the choice and use of a contraceptive method and its acceptance, (2) the importance of contraception for women, (3) the education and acquisition of adequate contraceptive knowledge, (4) the women's social status. Discussion and conclusion: Results of the research indicate that contraception is an important dimension of women's quality of life and their social status. The acceptance of contraception and the selection of a contraceptive method are influenced by a number of social factors and guided by various support systems. The knowledge of these factors enables nurses to systematically plan and deliver health education. Further research of the phenomenon could be conducted also among urban female population.
Keywords: družba; family planning; fenomenologija; health literacy; kakovost življenja; načrtovanje družine; phenomenology; quality of life; society; standard of living